PHK Pekerja/Buruh di Indonesia Berdasarkan Pasal 52 Ayat (2) Peraturan Pemerintah Nomor 35 Tahun 2021 - Mustakim, Mustakim (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2025)
The number of cases of industrial relations disputes, especially layoffs for reasons of misconduct is urgent after the enactment of Government Regulation number 35/2021. This provision indicates evidence of the failure of the state's role to provide protection, guarantee and responsibility for the balance and position between employers and workers. This paper aims to determine the applicability of Article 52 paragraph (2) of Government Regulation number 35/2021 in the Indonesian legal system and the settlement mechanism. This writing uses a normative juridical research method with a statutory, conceptual, and comparative approach based on relevant legal materials collected and analyzed. Because the violation is urgent, the method of terminating employment cannot be justified, so it must use the industrial relations dispute resolution method stipulated in Law Number 2 of 2004 concerning Industrial Relations Dispute Resolution.